2018
DOI: 10.1126/scisignal.aat8335
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial Ras/Rap1 site-specific endopeptidase RRSP cleaves Ras through an atypical mechanism to disrupt Ras-ERK signaling

Abstract: The Ras-ERK (extracellular signal–regulated kinase) pathway is critical for controlling cell proliferation, and its aberrant activation drives the growth of various cancers. Because many pathogens produce toxins that inhibit Ras activity, efforts to develop effective Ras inhibitors for treating cancer could be informed by studies of Ras inhibition by pathogens. Vibrio vulnificus causes fatal infections in a manner that depends upon multifunctional-autoprocessing repeats-in-toxin (MARTX), a toxin that releases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 81 publications
0
38
0
Order By: Relevance
“…Notably, depletion of RAS and reduction in pERK were also observed in spheroids treated with the catalytically-inactive mutant RRSP*-DTB, but at a 10-fold higher dose. Previous binding studies showed that RRSP* retains its ability to bind recombinant KRAS, especially at high KRAS:RRSP* molar ratios (Biancucci et al, 2018). Therefore, although RRSP*-DTB does not cleave RAS, it might impact its activity when used at high doses and after longer exposure both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Notably, depletion of RAS and reduction in pERK were also observed in spheroids treated with the catalytically-inactive mutant RRSP*-DTB, but at a 10-fold higher dose. Previous binding studies showed that RRSP* retains its ability to bind recombinant KRAS, especially at high KRAS:RRSP* molar ratios (Biancucci et al, 2018). Therefore, although RRSP*-DTB does not cleave RAS, it might impact its activity when used at high doses and after longer exposure both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…Imaging System (LI-COR Biosciences) and quantified by densitometry using NIH ImageJ software. Percentage of uncleaved RAS was calculated as previously described (Biancucci et al, 2018).…”
Section: Antibodiesmentioning
confidence: 99%
See 3 more Smart Citations